2017
DOI: 10.1177/0890117116685426
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Parents to Promote Children’s Nutrition and Health

Abstract: Policy and environmental changes were recommended for fostering a respectful relationship and building a bridge between providers and parents to improve communication about children's nutrition and health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
74
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 32 publications
5
74
1
Order By: Relevance
“…However, we did not ask sites if serving food, in general, was cost prohibitive. Previous studies have shown providers have limited funding to support improving the nutritional quality of menus 23 or experience increased food costs when menu quality increases. 24,25 Limitations Survey results may not fully capture practices at each site, as providers reported on a single day of foods and beverages served and may have biased reporting in favor of desirable rather than actual practice.…”
mentioning
confidence: 99%
“…However, we did not ask sites if serving food, in general, was cost prohibitive. Previous studies have shown providers have limited funding to support improving the nutritional quality of menus 23 or experience increased food costs when menu quality increases. 24,25 Limitations Survey results may not fully capture practices at each site, as providers reported on a single day of foods and beverages served and may have biased reporting in favor of desirable rather than actual practice.…”
mentioning
confidence: 99%
“…Lack of parental support or lack of parent engagement is ubiquitous across studies similar to this one (Lyn et al, 2014;Rosenthal et al, 2013). However, one interesting difference we found was that the providers in this study did not express trepidation in offending parents as others have expressed (Dev, Byrd-Williams, et al, 2017;Sisson et al, 2017). This may have been a result of the CCC providers feeling empowered to deliver the HC2 health messages to parents as a result of receiving training and education on how to do so from a university-led trainthe-trainers team.…”
Section: Discussionmentioning
confidence: 75%
“…Parents and supervisors can, for instance, make agreements on the foods that should be offered to the child. However, there are numerous barriers for communication between child-care providers and parents, including parents being too busy and child-care providers being afraid to offend parents [ 52 ]. Clear, written policies can facilitate communication [ 52 ], giving child-care workers a tool they can refer to and fall back on.…”
Section: Discussionmentioning
confidence: 99%